2022
DOI: 10.1111/imj.15661
|View full text |Cite
|
Sign up to set email alerts
|

The emerging association between bronchiectasis and systemic sclerosis: assessing prevalence and potential causality

Abstract: Background: Bronchiectasis has been observed in association with systemic sclerosis (SSc). Theorised aetiology includes aspiration related to oesophageal dysmotility, immunosuppressant medication use and the direct effect of collagen deposition on airway calibre.Aims: To detail bronchiectasis prevalence in an SSc population who have had a highresolution computed tomography (HRCT) of the thorax. We assessed whether oesophageal dysmotility, demographic variables, SSc duration or subclass were associated with bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Results from the Australian Scleroderma Cohort Study reported that 16.4% and 95.7% out of 256 patients had bronchiectasis and oesophageal dysmotility, respectively. A negative association between bronchiectasis and ILD was observed (75). Ostojic et al reported the presence of small airway obstruction in 66.6% of SSc patients.…”
Section: Pulmonary Involvementmentioning
confidence: 92%
“…Results from the Australian Scleroderma Cohort Study reported that 16.4% and 95.7% out of 256 patients had bronchiectasis and oesophageal dysmotility, respectively. A negative association between bronchiectasis and ILD was observed (75). Ostojic et al reported the presence of small airway obstruction in 66.6% of SSc patients.…”
Section: Pulmonary Involvementmentioning
confidence: 92%
“…Previous studies reporting the prevalence of bronchiectasis in patients with systemic sclerosis were based on small cohorts of systemic sclerosis (the largest study population was 256). In this regard, the prevalence of bronchiectasis in systemic sclerosis was reported to range widely from 3.3-59.1% [9][10][11]. To overcome the limitation of a small study population in previous studies, our study included a large number of individuals with systemic sclerosis (n = 4,485) and revealed that about 5.5% of individuals with systemic sclerosis developed new bronchiectasis during a median 6-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Non-cystic brosis bronchiectasis (hereafter referred to as bronchiectasis) is a chronic lung disease characterized radiologically by permanent bronchial dilatation and clinically by the presence of cough, sputum, and recurrent chest infections [8]. A few systemic sclerosis cohort studies have reported that bronchiectasis is a common pulmonary comorbidity in patients with systemic sclerosis, ranging from 3.3-59.1% [9][10][11]. However, it is not well known whether the risk of incident bronchiectasis is higher in patients with systemic sclerosis due to small study populations and the absence of comparable controls [9][10][11].…”
Section: Backgroudmentioning
confidence: 99%
See 1 more Smart Citation
“…Connective tissue diseases (CTD) related to autoimmune diseases, such as rheumatoid arthritis, Sjögren syndrome, or systemic sclerosis, have been viewed as risk factors of bronchiectasis [4] because they are frequently concomitant diseases [71][72][73]. The reasons may be associated, in some cases, with the use of immunosuppressive therapies such as mycophenolate mofetil, believed to induce hypogammaglobulinemia [74].…”
Section: Potential Connections Between Connective Tissue Diseases Cil...mentioning
confidence: 99%